Self Disclosure dan Tingkat Stres pada Mahasiswa yang sedang Mengerjakan Skripsi - Witrin Gamayanti; Mahardianisa Mahardianisa; Isop Syafei (Psympathic : Jurnal Ilmiah Psikologi, 2018)
Students often experience stress that comes from academic activities. For final-year students, finishing a thesis often become a stressor. Symptoms of stress in students are feeling tired, anxious, not eager to do the thesis. The impact is the thesis is delayed and the students chose to forget it, avoided their lecturers, complained in the social media about the difficulties encountered and ultimately delayed the study period. When experiencing stress, students share their problems to the peer group to get a solution or just to relieve his feelings, called self disclosure. This study aims to determine the influence of self disclosure on stress levels, using method of correlation with simple linear regression analysis. The measuring instrument were the Revised Self Disclosure Scale and the Student-Life Stress Inventory. The participants were 49 students of psychology UIN who are working on thesis. The results showed no influence of self disclosure toward stress levels.